Implementasi Masterplan Smart City Dalam Menghadirkan Pelayanan Berbasis Digital Di Kecamatan Samarinda Utara - Nanang Setiawan; Iman Surya (Jurnal Ilmu Pemerintahan, 2024)
This study aims to explain what the implementation of Mayor Regulation Number 8 of 2018 concerning Smart City Masterplan in the implementation of Digital-Based Government System in North Samarinda Sub-district is like and to identify things that hinder the implementation of Mayor Regulation Number 8 of 2018 concerning Samarinda Smart City Masterplan in the implementation of Digital-Based Government System in North Samarinda Sub-district. The method used is descriptive qualitative by collecting data through interviews, observation, and documentation. The results showed that policy communication in some areas faced challenges in transmission, clarity, and consistency, causing confusion and limited understanding and involvement of policy actors and the community. Limited trained human resources, budgets and facilities also hamper policy implementation, making careful budget planning, technology training and investment in equipment essential. However, the government's proactive and collaborative stance, supported by the private sector through CSR, has accelerated policy implementation, encouraged digital infrastructure development, and improved the quality of public services.